Load Flow Using Newton Raphson Method - Wahid, Mohd Akhmal (Universiti Sains Malaysia, 2005)
The model of the electric power system that is used in a power flow analysis consist of all the busses in the system, the generating units and load elements connected to these various buses, and the transmission lines that interconnected the buses. The information furnished by a power flow analysis is quite simply the voltage profile of the system. In other words, the important result of the analysis is the determination of the voltage magnitude and its associated phase angle at each bus. Of course, once this information is known, it is a routine matter to determine the currents in each transmission link, and accordingly, the real and reactive power flows. Conclusions regarding overloads on any of the system components are obtained at this point in the study. They are necessary for planning operation, economic scheduling and exchange of power between utilities. In addition, power flow analysis is required for many other analyses such as transient stability and contingency studies. The most common techniques used for the iterative solution of nonlinear algebraic equations are Gauss-Seidel, Newton –Raphson, and Quasi-Newton methods. Because of its quadratic convergence, Newton’s method is mathematically superior to the Gauss-Seidel method and is less prone to divergence with ill-conditioned problems. For large power systems, the Newton- Raphson method is found to be more efficient and practical. The number of iterations required to obtain the solution is independent of the system size, but more functional evaluations are required at each iteration. This project presents Newton-Raphson method for conducting load flow. A practical IEEE-5 bus system is considered for illustrator. A software in MATLAB is written and load flow is simulated. The results are compared with the programs written by Hadi Saadat and presented in the Chapter 4.